Поезія Оксани Забужко «Задзеркалля: пані Мержинська»:драматизація метатексту - Вісич, Олександра; Visych, Oleksandra (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена аналізу поезії Оксани Забужко «Задзеркалля: пані Мержинська» та розмаїття форм метатексту в ній. Окрему увагу приділено засобам драматизації в цьому ліричному творі. Доведено, що метатекстуальні компоненти на кшталт біографії Лесі Українки й алюзій на її твори створюють ефект міні-п’єси. This article analyzes the poetry of Oksana Zabuzhko “Through the Looking Glass: Mrs Merzhynska”, in particular, we study the diversity of metatext in it. Among others it is chosen such options of metatext as an explanatory mechanism, self-consciousness of literature aimed at understanding the nature of creative work; moreover external construction on relation to the text. Special attention is paid to the means of dramatization of lyrical work at the level of pathos that is marked by a abrupt change in emotional tone; as well as at the level of subjective and spatiotemporal organization of the work and its dramatic comparison. It is proved that the poem of Zabuzhko has two objects of comparison. They are a fictional character from the alternative history of life on the one hand and a conventionally real image of Lesia Ukrainka. It is found that metatext has been formed by several specific components: Lewis Carroll’s novel, biography and works of Lesia Ukrainka. Its function is in the creation of a specific “through-the-glass” time-space, and most importantly, lyrical dramatization of the poem and creation of the effect of mini-play.
The Poem of Oksana Zabuzhko “Through the Looking Glass: Mrs Merzhynska”: Dramatization of Metatext
Keywords: метатекст; драматизація лірики; трагедія; репліка; Леся Українка; metatext; dramatization of lyrics; tragady; replica; Lesia Ukrainka